(Dis)agreements in the management of conservation conflicts in the Calakmul Biosphere Reserve, Mexico. (12th December 2020) - Oliva, Malena; García-Frapolli, Eduardo; Porter-Bolland, Luciana; Montiel, Salvador
Summary: To manage widespread conservation conflicts, building a shared understanding among the parties involved has been considered key. However, there is little empirical evidence of the role this understanding might play in the context of imposed biosphere reserves. Using semi-structured and in-depth interviews in two communities within the Calakmul Biosphere Reserve, we explored whether or not there is a shared understanding of conflicts between local people and reserve managers, and we analysed its contribution to conflict management. We found that a shared understanding is not a determining factor when the conflict solution demands actions that exceed stakeholders' functions. While a shared understanding helps with the global process of conflict management, there are other challenges: local impairment resulting from the exclusionary creation and the operation of protected areas and the need for action to solve a conflict that exceeds the functions of stakeholders.